'Memory' of the stratum corneum: exploration of the epidermis' past. (September 2014) - Haftek, M.
Summary: The stratum corneum (SC) is the final product of the process of epidermal differentiation. Besides its crucial protective role as a physical permeability barrier, this composite structure made of cornified keratinocytes embedded in a layered lipid matrix is also, by nature, a tissue that keeps track of past events occurring in the outermost living layers. In normal human epidermis, formation of the SC is very rapid, and during this cornification process several structures expressed by the last granular layer of keratinocytes become entrapped and immobilized at the cells' periphery. Cell–cell junctions are obvious targets of transglutaminases that cross‐link junctions' components within the corneocyte envelopes. Thus, desmosomes and tight junctions (TJs) in living cells become fixed at the corneocyte periphery and cannot be recycled anymore. We have quantified the TJ‐like structures residing in the SC of human skin explants subjected to environmental stress and compared these results with fresh skin controls. Significant overexpression of TJ‐like cell–cell envelope fusions has been observed in the stressed epidermis and in two different hereditary skin diseases characterized by increased SC cohesion. Quantitation of TJ‐like structures has contributed to the interpretation of the diseases' physiopathology. Other examples of information retrieved from the SC concern fluctuating lipid expression in the course of atopic dermatitis and patterns of corneodesmosome breakdown influencing SC desquamation. It is, therefore, possible to analyse and quantify the traces left in the SC and to draw conclusions on the dynamics of living tissue over the past several days. Abstract : What's already known about this topic? Although it is common sense that traces of the living cell activity should persist in the cornified remnants forming the horny layer, the practical exploitation of this fact was not so far fully implemented. What does this study add? Some relevant examples of exploring the epidermis' past activity through qualitative and quantitative investigation of the SC are recapitulated here.